Dampak vaksinasi pertama covid-19 terhadap abnormal return dan trading volume activity pada perusahaan yang terdaftar dalam lq45 di bursa efek indonesia - Nifta Ilmayanti; Aimatul Yumna (Universitas Negeri Padang, 2021)
The first Covid-19 vaccination event given to Mr. Joko Widodo as President of the Republic of Indonesia is an important event during the Covid-19 pandemic, and this event is considered to contain information that can affect the capital market. This information can provide a signal to investors in making their investment decisions. The signal can be a positive signal and sometimes it can be a negative signal. These two signals can certainly make the stock market react. To find out how the market reacts to these events, it can be seen from difference in abnormal returns and trading volume activity in the capital market. The event study in this research was conducted by observing the abnormal return and trading volume activity on the Indonesia Stock Exchange. And the samples in this study are companies listed in LQ45 on the Indonesia Stock Exchange. Because this research is based on event studies, it requires issuers that are liquid, so that measurements can be carried out immediately and produce relatively accurate results. Keyword : The first Covid-19 Vaccination Event, Abnormal Retutn, and Trading Volume Activity